EFEKTIVITAS MEDIA DIGITAL TERHADAP PRESTASI BELAJAR AL-QUR’AN SISWA SEKOLAH DASAR - Afifah; Imam Mashuri; Nasrodin (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2025)
The purpose of this study was to determine the use of digital media in student learning in the Quran, the level of student achievement, and the impact of digital media use on student achievement in learning the Quran at SDN Dukuh Kupang III Surabaya. Data collection techniques used in this study were questionnaires, observation, and documentation. The population in this study was all fourth-grade students at SDN Dukuh Kupang III Surabaya, totaling 131 students, from which 34 samples were taken. Data analysis used percentage analysis and product-moment analysis techniques. The results of this study indicate that at SDN Dukuh Kupang III Surabaya, digital media use was categorized as moderate (88%), student achievement in learning the Quran was categorized as moderate (85%), and there was an influence of digital media use on student achievement in learning the Quran, as shown by the product moment calculation (rxy = 1) with a significance level of 5% = 0.339, meaning rxy > rtable, thus accepting the alternative hypothesis (Ha) and rejecting the null hypothesis (Ho). The result of rxy = 1 was consulted in the correlation coefficient table, with the r value in the interval 0.90–1.00, indicating a very high influence.